Developing a Mathematics Curriculum for the Biosciences. Issue 2 (7th February 2022) - Gordon, Sheldon P.; Gross, Sarah; Bahamonde, Matthew; Winn, Jack; Seifert, Jessica; Martin, Carla A.; Yang, Yajun
Abstract : This article describes the authors' experiences developing and implementing an innovative curriculum connecting mathematics and the biological sciences. It describes the original plan, the modifications that were necessary, and some advice to readers who might want to develop comparable programs.